Investigation on biochemical plant factors associated with resistance against insect pests in Black Gram - Sreedhar, B K; Thumar, R K; Dhruve, J J; Pathan, Naziya P (Indian Journal of Plant Protection, 2025)
A laboratory experiment was carried on role of biochemical constituents against insect pests in black gram at Department of Biochemistry, Anand Agricultural University, Anand, Gujarat during 2019 and 2020. The biochemical factors viz., total phenol, total soluble sugars, crude protein, moisture and total chlorophyll were estimated in different genotypes/varieties of black gram. Among the genotypes, PANT-U-31recorded the highest phenol content in leaf, flower and pod followed by DBUGP-16-1. Phenols exhibited highly significant negative correlation with the insect-pests indicating major role in imparting the resistance in black gram genotypes. Other biochemical parameters showed a significant positive association with the insect-pests. The highly significant positive association between incidence of insect pests on black gram genotypes and their biochemical constituent’s viz., total soluble sugar, crude protein, moisture and total chlorophyll content clearly indicated the significant role of these compounds on pest incidence. The resistant genotypes had low amount of TSS, crude protein, moisture and chlorophyll content in contrast to phenol. The total phenol content showed highly significant negative correlation with whitefly (r=-0.87**), jassid (r=-0.90**) flower thrips (r=-0.79**), Bihar hairy caterpillar (r=-0.93**), spotted pod borer (r=- 0.92**) and leaf eating caterpillar exhibited (r=-0.65*) significant negative correlation with phenol which plays a significant role in defense mechanism.